Analisis Ushul Fikih terhadap Praktik Akad Istisna' dalam Pemesanan Tralis di Desa Jlamprang Kecamatan Wonosobo - wisnu futuchal arif wisnu arif (Program Studi Hukum Ekonomi Syariah, 2026)
The practice of the istisna' contract in custom-made iron grille transactions represents a form of Islamic commercial dealing that has developed in response to community needs and local customs. This study aims to analyze the implementation of the istisna' contract in iron grille orders in Jlamprang Village, Wonosobo District, through the perspective of Islamic legal theory (uṣūl al-fiqh). This research employed a qualitative field research approach. Data were collected through observations, interviews, and documentation, and analyzed descriptively using the theories of 'urf (custom), maṣlaḥah mursalah (public interest), and sadd al-dharī'ah (blocking the means to harm). The findings indicate that transactions are generally conducted through verbal agreements, payments are commonly made after the work is completed, while technical specifications and completion schedules are largely determined based on established local customs. From the perspective of uṣūl al-fiqh, these practices are generally acceptable because they reflect valid custom ('urf ṣaḥīḥ) and provide benefits for the contracting parties. Nevertheless, potential legal risks remain due to unclear product specifications, uncertain completion deadlines, and post-contract price adjustments. Therefore, greater contractual clarity is required to ensure legal certainty, fairness, and conformity with the objectives of Islamic law